Inferred father-to-son transmission of herpes simplex virus results in near-perfect preservation of viral genome identity and in vivo phenotypes. Issue 1 (December 2017) - Pandey, Utsav; Renner, Daniel; Thompson, Richard L.; Szpara, Moriah; Sawtell, Nancy M.
Abstract High throughout sequencing has provided an unprecedented view of the circulating diversity of all classes of human herpesviruses. For herpes simplex virus 1 (HSV-1), we and others have previously published data demonstrating sequence diversity between hosts. However the extent of variation during transmission events, or in one host over years of chronic infection, remain unknown. Here we present an initial example of full characterization of viruses isolated from a father to son transmission event. The likely occasion of transmission occurred 17 years before the strains were isolated, enabling a first view of the degree of virus conservation after decades of recurrences, including transmission and adaptation to a new host. We have characterized the pathogenicity of these strains in a mouse ocular model of infection, and sequenced the full viral genomes. Surprisingly, we find that these two viruses have preserved their phenotype and genotype nearly perfectly during inferred transmission from father to son, and during nearly two decades of episodes of recurrent disease in each human host. Given the close genetic relationship of these two hosts, it remains to be seen whether or not this conservation of sequence will occur during non-familial transmission events.